2020
DOI: 10.1186/s13293-020-00329-0
|View full text |Cite
|
Sign up to set email alerts
|

Role for ovarian hormones in purinoceptor-dependent natriuresis

Abstract: Background Premenopausal women have a lower risk of hypertension compared to age-matched men and postmenopausal women. P2Y2 and P2Y4 purinoceptor can be considered potential contributors to hypertension due to their emerging roles in regulating renal tubular Na+ transport. Activation of these receptors inhibits epithelial Na+ channel activity (ENaC) via a phospholipase C (PLC)-dependent pathway resulting in natriuresis. We recently reported that activation of P2Y2 and P2Y4 receptors in the renal medulla by UTP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…It is important to consider the potential contribution of the various Na + regulatory pathways to sex-differences in natriuresis during acclimation to dietary salt challenges. Evidence implicates roles for Na + transporters [ 46 , 47 ], aldosterone signaling [ 46 , 48 ], and purinergic signaling [ 49 51 ] in eliciting sex-differences in renal salt handling and blood pressure regulation. Further, it has been shown that sex hormones and their downstream signaling cascades contribute to the natriuretic capacity of the kidney and consequently hypertension development.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to consider the potential contribution of the various Na + regulatory pathways to sex-differences in natriuresis during acclimation to dietary salt challenges. Evidence implicates roles for Na + transporters [ 46 , 47 ], aldosterone signaling [ 46 , 48 ], and purinergic signaling [ 49 51 ] in eliciting sex-differences in renal salt handling and blood pressure regulation. Further, it has been shown that sex hormones and their downstream signaling cascades contribute to the natriuretic capacity of the kidney and consequently hypertension development.…”
Section: Discussionmentioning
confidence: 99%